Optimization and Integration Strategies for Hybrid Renewable Energy Systems in the Brazilian Power Grid: A Systematic Review - Dalton F. Guedes Filho; Rodrigo L. Miranda; Lucas A. Correia; Lucas do E. S. Fernandes; Ricardo C. Medrado; Marcio De C. Filho; Jose B. M. Filho; Manoel H. N. Marinho; Erick G. Sperandio Nascimento (IEEE Access)
The global transition to renewable energy requires efficient Hybrid Renewable Energy Systems (HRES) to mitigate the intermittency of solar and wind power. This paper presents a review of HRES design and optimization methodologies, emphasizing their integration into the national power grid. We analyze optimization techniques, including metaheuristic algorithms and simulation tools such as HOMER, in addition to regulatory and operational challenges. A systematic literature review was conducted using Scopus, applying bibliometric analysis to identify trends in HRES research. Our findings highlight critical gaps in optimization strategies, energy storage integration, and economic feasibility analysis. This study provides insights for researchers and policymakers to enhance the reliability and efficiency of HRES in large-scale grid applications.